Do athletes' responses to coach autonomy support and control depend on the situation and athletes' personal motivation?. (July 2019) - Delrue, Jochen; Soenens, Bart; Morbée, Sofie; Vansteenkiste, Maarten; Haerens, Leen
Abstract: Although plenty of studies have shown that a controlling, relative to an autonomy-supportive, motivating style yields a host of undesirable outcomes, at least some sport coaches endorse the belief that in some situations (e.g., when athletes misbehave) or with some athletes (e.g., those who are amotivated) a controlling approach is warranted and even beneficial. On the basis of Self-Determination Theory (Deci & Ryan, 1985; Ryan & Deci, 2017), the current study examined to what extent the effects of an autonomy-supportive and controlling coaching style depend on (a) the situation at hand and (b) athletes' personal motivation. To do so, we made use of an experimental vignette–based approach. Specifically, after having completed a validated questionnaire on their motivation to practice judo (i.e., autonomous motivation, controlled motivation, amotivation), 101 judokas (67.3% boys; Mage = 13.31 ± 1.54) were randomly assigned to either an autonomy-supportive or a controlling condition. In each condition, judokas read two comics representing distinct situations (i.e., athletes struggling with skill mastery despite their effort versus athletes not putting effort and disturbing practice), imagining themselves being the athlete in the comic. Having read the comic, athletes filled out a paper and pencil questionnaire in which they rated their anticipated need satisfaction/frustration, engagement, oppositional defiance, and anger. Results showed that the situational circumstances (i.e., athletes are misbehaving) attenuated, yet, did not cancel out, some of the detrimental effects of a controlling (relative to an autonomy-supportive) approach. Effects of coaches' motivating style appeared to be largely independent of athletes' motivation. The theoretical and practical significance of the results are discussed. Highlights: Moderation of situational circumstances on effects of coach autonomy support and control. The positive effects of coach autonomy support and the negative effects of coach control are evident, These effects are evident, both when athletes disturb practice and when they struggle with an exercise. Effects of control are somewhat less negative when athletes are disturbing practice. Effects of coach autonomy support and control are largely independent of athletes' type of motivation.